Representations and cohomologies of modified λ-differential Hom-Lie algebras - Yunpeng Xiao; Wen Teng (AIMS Mathematics, 2024)
In this paper, we introduce the concept and representations of modified $ λ $-differential Hom-Lie algebras. We then develop the cohomology of modified $ λ $-differential Hom-Lie algebras with coefficients in a suitable representation. As applications, abelian extensions and skeletal modified $ λ $-differential Hom-Lie 2-algebras are characterized in terms of cohomology groups.